Efektivitas Teknik Tanam dan Jarak Tanam terhadap Pertumbuhan dan Produksi Selada Merah (Lactuca sativa var. Crispa) pada Wiremesh Tower Garden: Effectivity of Planting Techniques and Spacing on Growth and Production of Red Lettuce (Lactuva sativa var. Crispa) in Wiremesh Tower Garden - Yulianti, Anggie; Puspitawati, Mutiara Dewi; Warid (Politeknik Pertanian Bogor, 2024)
Red lettuce (Lactuca sativa var. Crispa) is a leaf vegetable plant that has curly or wavy leaf shapes and reddish green color. This plant is favored by urban communities in the city because it has good nutritional value, is easy to grow, and is aesthetically pleasing. The limited space owned by the grower is the main obstacle in the cultivation of red lettuce in the city so that vertical or vertical cultivation techniques are needed. The vertical technique used is Wiremesh Tower Garden (WTG) verticulture. The aim of the study was to compare the effectiveness of the growth and production of red lettuce in WTG with conventional cultivation in the field. The environmental design used was a Randomized Block Design (RAK) which consisted of two factors, namely cultivation techniques as the first factor consisting of WTG and conventional/open land. While the spacing is the second factor which consists of 10x12 cm and 20x24 cm. The results of this study indicate that the wiremesh tower garden planting technique provides more efficient results in the cultivation of red lettuce. Spacing of 10x12 cm in the WTG planting technique gave good results for the variables of leaf width, number of leaves, crown fresh weight, root wet weight, production weight, and vitamin C content. The use of WTG planting technique with a spacing of 10x12 cm gave effective results in red lettuce cultivation, because the results of growth and production were not significantly different from planting techniques on land at the same spacing